An interactive graphical interface tool for parameter calibration, sensitivity analysis, uncertainty analysis, and visualization for the Soil and Water Assessment Tool. (October 2022) - Nguyen, Tam V.; Dietrich, Jörg; Dang, Thanh Duc; Tran, Dang An; Van Doan, Binh; Sarrazin, Fanny J.; Abbaspour, Karim; Srinivasan, Raghavan
Abstract: The Soil and Water Assessment Tool (SWAT) is one of the most widely used and well-tested eco-hydrological models. However, parameter calibration, sensitivity analysis and uncertainty analysis remain among the most challenging tasks. Existing SWAT parameter calibration, sensitivity analysis, and uncertainty analysis tools are either commercial products or free tools with limited options. This study demonstrates an interactive graphical user interface tool in the R environment for SWAT parameter calibration, sensitivity and uncertainty analyses, and visualization, called R-SWAT . Different R functions/packages for parameter calibration, sensitivity analysis, and uncertainty analysis have been incorporated into R-SWAT . Third-party packages can be integrated into R-SWAT with minimum effort. The application of R-SWAT for a test case study demonstrates its functionalities. In general, R-SWAT (1) is a potential platform for developing and testing new sensitivity or optimization packages, and (2) promotes the understanding of hydrological processes with open-source SWAT and R. Highlights: An R tool for SWAT parameter calibration, sensitivity analysis, and uncertainty analysis is introduced. Integration with new sensitivity or optimization packages is streamlined. The proposed tool enhances hydrological research with SWAT and R.